PENGARUH DIVIDEND YIELD DAN PRICE EARNINGS RATIO TERHADAP RETURN SAHAM DENGAN INVESTMENT OPPORTUNITY SET SEBAGAI VARIABEL MODERATING - RIKI MARTUSA (Jurnal Bisnis dan Akuntansi, 2007)
This research is aimed to examine and find out empirical evidence of (1) the influence of dividend yield on stock return with investment opportunity set as the moderating variable, (2) the influence of price earnings ratio on stock return with investment opportunity set as the moderating variable. The using of investment opportunity set is aimed to search influence between dividend yield and price earnings ratio with stock return. As model used in this study, dividend and retained earnings has reflected the use of dividend yield and price earnings ratio by market participants. Samples used in this research are manufacturing companies listed in Bursa Efek Jakarta in 5 years observation period (1999-2004). Total samples are 30 companies. The data are collected using purposive sampling method. The result of moderated regression analysis (MRA) shows that (1) dividend yield does not influence stock return with investment opportunity set as the moderating variable, (2) price earnings ratio does not influence stock return with investment opportunity set as the moderating variable. Thus, the hypothesis of the research is not empirically supported.